The Intrinsic and Extrinsic Proprieties of Things. Is Kant a Structural Realist? - Castrejón Mendoza, José Gilberto (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In current debates on scientific realism, it is common to characterize Kant as an idealist for whom reality of things, as it is in itself, is outside our scope of knowledge. The article locates transcendental idealism against a realistic position called structural realism, via the interpretation given by Rae Langton in her text Kantian Humility, where the author tries to respond to the problem of double affection, considering two types of properties of things: the intrinsic and the relational, which will make it possible to establish a bridge between said interpretation and structural realism. The conclusion is that, given this interpretive path, it is possible to locate Kant in the debate on scientific realism, despite the charge that this does not go through idealism.